Development and acceptability of burgers made from Selaroides leptolepsis and Aristichthys nobilis - Yu, Swee Yean; Siah, Watt Moey (Asian Fisheries Society, 1998)
Fishburgers were developed from Selaroides leptolepis and Aristichthys nobilis. Inhouse sensory evaluation showed that the formulation with a ratio of 40:60 S. leptolepis to A. nobilis was most acceptable. A market trial of the product showed good acceptability in terms of taste, texture, color and juiciness. 52.8% of the respondents were willing to purchase the fishburgers at a price range of US$2.24 to US$2.60.